Cloud Infrastructure Fortification: Advanced Security Strategies in the Era of Emerging Threats - Sandeep Batchu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of advanced strategies for protecting cloud infrastructure against emerging cybersecurity threats. The article examines the transformation from traditional perimeter-based security models to adaptive, multi-layered defense mechanisms, emphasizing the critical role of zero-trust architectures and artificial intelligence in modern cloud security. Through case studies and empirical analysis, the article investigates the implementation of advanced encryption technologies, multi-cloud strategies, and automated threat detection systems across various organizations. The article demonstrates how the integration of machine learning-driven security solutions with robust incident response frameworks significantly enhances threat detection and mitigation capabilities. The article indicates that organizations adopting these advanced security measures demonstrate improved resilience against sophisticated cyber attacks while maintaining operational efficiency. The article contributes to the growing body of knowledge in cloud security by providing a structured framework for implementing comprehensive security strategies that address current and emerging threats in cloud environments.
Keywords: Zero-trust architecture; Cloud infrastructure security; AI-driven threat detection; Multi-cloud strategy; Homomorphic encryption